2015
DOI: 10.1155/2015/359640
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Sleep Disturbance among Liver Diseases in Long-Term Transplant Survivors

Abstract: Sleep parameters for patients who undergo LT for hepatitis C do not improve following LT as much as they do in patients transplanted for ETOH. Following LT, patients transplanted for ETOH are significantly more satisfied with their sleep than those transplanted for hepatitis C. Physicians should address and manage sleep quality after LT, so as to ultimately improve quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
0
8
2
Order By: Relevance
“…The findings suggest that sleep disturbance is a highly prevalent symptom experienced after liver transplantation. The mean total sleep time reported by the participants was 6.01 hours (SD = 1.50), which is less than in previous studies on liver transplant recipients (6.6-7.0 hours; Bhat et al, 2015;Mendes et al, 2014;Reilly-Spong et al, 2013).…”
Section: Sleep Qualitycontrasting
confidence: 64%
“…The findings suggest that sleep disturbance is a highly prevalent symptom experienced after liver transplantation. The mean total sleep time reported by the participants was 6.01 hours (SD = 1.50), which is less than in previous studies on liver transplant recipients (6.6-7.0 hours; Bhat et al, 2015;Mendes et al, 2014;Reilly-Spong et al, 2013).…”
Section: Sleep Qualitycontrasting
confidence: 64%
“…On the other hand, patients with liver disease and cirrhosis show perturbed sleep and daily rhythm of body temperature ( 105 , 106 ). Decreased testosterone and GH levels as well as sleep problems caused by NAFLD are improved after liver transplantation, suggesting that the liver could play a role in these endocrine and circadian perturbations ( 107 109 ). However, inactivating Bmal1 only in hepatocytes has no impact on the circadian rhythm of the animals ( 11 ) and is not sufficient to drive the endocrine perturbations observed in animals with a global deletion of Bmal1 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It was worth noting that 50.0% of recipients had excessive urination at night, about half of the recipients woke up in the middle of the night or early in the morning, and over one-third took more than 30 minutes to fall asleep. Recent studies have confirmed that waking up in the middle of the night, nocturia (excessive urination at night), and difficulty falling asleep were common issues for liver transplant recipients [4,28], but the causes and details of these symptoms have not been studied. In addition, it should be emphasized that only 10.48% of patients reported the use of hypnotic medication in the past month, which is less than that reported by Rodrigue (62.1%) [4].…”
Section: Discussionmentioning
confidence: 99%